A Five-Year Review of Feto-Maternal Outcome of Antepartum Haemorrhage in a Tertiary Center in Nigeria - Oguejiofor, Charlotte; Okafor, Chidimma; Eleje, George; Ikechebelu, Joseph; Okafor, Chigozie; Ugboaja, Joseph; Ogabido, Chukwudi; Njoku, Tobechi; Umeononihu, Osita; Okpala, Boniface; Nwankwo, Malarchy; Ezeigwe, Chijioke; et al. (International Journal of Innovative Research in Medical Science, 2023)
Background: Pregnancies complicated with antepartum-haemorrhage is high risk pregnancies associated with adverse maternal, fetal-and-perinatal-outcomes. It contributes significantly to fetal and maternal mortality especially in the developing countries. Proper antenatal care and prompt intervention is necessary to forestall adverse and improve outcome. Objective: To determine the prevalence, sociodemographic characteristics, risk factors, fetomaternal outcome of pregnancies with antepartum haemorrhage. Methods: The case files of the patients were retrieved from the medical records department. The total number of deliveries within the study period was obtained from the labour ward records. The feto-maternal-outcome-measures were; prevalence of caesarean-section, postpartum-haemorrhage, hysterectomy, need for blood-transfusion, maternal-death, prematurity, need for admission in intensive-care-unit and still births. The data was analysed using SPSS version 21. Chi-square was used to test for significance. Results: Within the 5-year period under review, out of a total of 6974 deliveries, 234 had antepartum-haemorrhage (3.4% prevalence rate). Abruptio-placentae was the commonest cause and accounted for 69.5% of the cases (prevalence of 2.1%) while placenta praevia accounted for 28.2% of the cases (prevalence rate of 0.9%). The mean age of the women was 31.8±5.3 years. The mean parity was 3.4±1.7 and majority (63.8%) of the women were unbooked. The commonest identifiable risk factors were multiparity and advanced maternal age. One-hundred-and sixty-six (77.9%) women were delivered through the abdominal route. Postpartum-haemorrhage occurred in 22.1% (47) of the cases while prematurity was the commonest fetal complications. Maternal mortality was 0.47% (1) while still birth was 44.1% (94). Conclusion: There is high prevalence of antepartum-haemorrhage in our environment. Abruptio-placentae was the commonest cause and associated with significant adverse fetomaternal-outcome when compared with placenta-praevia. Thus, good and quality antenatal care as well as high index of suspicion, prompt diagnosis and treatment remain the key to forestall these complications and improve fetomaternal-outcome.